IDENTITY POLITICS AND SYMBOLIC INTERACTIONS BETWEEN SUNDANESE AND JAVANESE IN INDONESIA - Haryono Haryono (CIC Lembaga Riset dan Konsultan Sosial, 2019)
Indonesia has a large area and a diverse society. Cultural diversity and social identity based on ethnicity. The analysis of this research uses a literature study approach from the results of research and journals discussing the politics of identity between Javanese and Sundanese. The results of the analysis found that, first, the politics of the Perang Bubat that occurred between Javanese and Sundanese, which has had an influence on Javanese and Sundanese society to this day. Second, the Perang Bubat can be used as a symbolic inetaraksi between Javanese and Sundanese in giving meaning to the Perang Bubat.